Beginning The Journey Of Informal Counseling From A Theistic Existential Approach: A Personal Perspective From A Catholic Christian (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
A Catholic Christian learns about the existential therapeutic approach in a counseling course in graduate school, and adapts it to his future work in pastoral ministry. He relates how a theistic existentialism best explains the human dilemma and what it means to live authentically from his religious perspective.
Keywords: Theistic existentialism; psychotherapy; Christianity; mindfulness; religion